Data evaluation of broiler chicken rearing and slaughter—An exploratory study - Junghans, Annika; Deseniß, Lea; Louton, Helen (Frontiers in Veterinary Science, 2022)
To process and evaluate the data from broiler fattening and slaughtering, we investigated the production data of 107 straight run flocks of the commercial meat-type breed Ross 308 (Aviagen, EU). All flocks were raised and slaughtered in Germany and the average slaughter age was 37 days. The health outcomes of interest were mortality, average weight and the slaughter results. First-week mortality, cumulative mortality, stocking density, flock size, season, production week of the parental flock, farm, antibiotic treatment and the interaction between antibiotic treatment and season were considered as possible influencing factors. The average first-week mortality (FWM) and cumulative mortality percentages were 0.66% and 2.74%, respectively. First-week mortality was influenced by flock size, production week of the parental flock and the interaction between antibiotic treatment and season, whereas cumulative mortality was influenced by antibiotic treatment, farm and first-week mortality. The average weight (mean 2.30 kg) was influenced by season, stocking density, flock size, farm and the interaction between antibiotic treatment and season. The condemnation rate was on average 1.48%, with the most common causes being deep dermatitis (mean 0.63%), ascites (mean 0.53%) and not suitable for production/general disease (mean 0.25%). Several factors influenced the causes of condemnation, with season being the most prominent one, followed by the interaction between antibiotic treatment and season, the antibiotic treatment alone and stocking density.